Programmed cell death 1 checkpoint inhibitors in the treatment of patients with advanced melanoma - Mackiewicz, Jacek; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2017)
The treatment landscape of advanced melanoma has changed significantly following the discovery and marketing authorisation of immune checkpoints inhibitors. Ipilimumab (anti-CTLA-4) was the first one to be approved, and it. demonstrated long-term survival in about 20% of patients. Subsequently, anti-programmed cell death-1 (a-PD-1) antibodies (pembrolizuamb, nivolumab), inhibitors of PD-1/programmed cell death-1 ligand (PD1-L) synapse, showed higher clinical efficacy with lower toxicity comparing to ipilimumab. The highest clinical benefit in patients was observed when nivolumab and ipiliumumab were combined. However, the above strategy, due to very high toxicity, has limitations for use in all patients with advanced melanoma. Notwithstanding, patients treated with anti-PD1 beyond disease progression benefit from treatment continuation; further studies are warranted in this indication. Furthermore, patients responding to treatment with anti-PD1 will benefit from the therapy after its discontinuation. Immune checkpoint inhibitors are clinically effective regardless of BRAF mutation. Currently there is no recommendation regarding which treatment option should be selected for the treatment of the population – immunotherapy or targeted therapy with BRAF and MEK inhibitors. Randomised trials are ongoing comparing these two treatment strategies in patients with BRAF mutation. Encouraging results were observed in early phase trials in patients receiving the combination of immune and targeted therapy. Phase 3 studies are underway. Patients with elevated serum lactate dehydrogenase present poor prognosis regardless of the systemic treatment used. novel treatment strategies should probably be developed for these patients.